PENGARUH PERSEPSI KEDISIPLINAN DIRI TERHADAP HASIL BELAJAR MATEMATIKA SISWA - Besse Intan Permatasari; Tri Hariyati Nur Indah Sari (De Fermat : Jurnal Pendidikan Matematika, 2022)
The purpose of this study was to determine whether the perception of self-discipline has an influence on students' mathematics learning outcomes. This is cross sectional survey research with quantitative approach. The research sample was randomly selected from the population (N = 64) and 55 students were chosen based on the Isaac & Michael table. Questionnaires were used to collect data on perception of self-discipline and passed the validity test and reliability test (Cronbach's Alpha coefficient = 0.71; considered as high reliability). Whereas, the data of mathematics learning outcomes were obtained from daily mathematics exams. Simple linear regression statistical analysis was used to proceed the data and the result showed that 7 students had perception of self-discipline in low category, 35 students in medium category, and 13 students in high category. Also, the perception of self-discipline has a positive linear relationship with mathematics learning outcomes and contributes 31.8% of the variance of mathematics learning outcomes (R = 0.564; R2 = 0.318; β1 = 1.679; p < 0.05). This research recommended to improve students’ self-discipline in enhancing students' mathematics learning outcomes.